Phosphorus incorporation in single‐walled carbon nanotubes produced by low‐pressure CVD. Issue 12 (4th November 2016) - Mendoza, C. D.; Freire, F. L.; Larrude, D. G.; Maia da Costa, M. E. H.
Abstract : The aim of this work is the synthesis and characterization of single‐walled carbon nanotubes with phosphorus incorporated. Two temperatures (800 and 850 °C) were used to produce the nanotubes in a low‐pressure chemical vapor deposition system using as precursor the solid substance triphenylphosphine without any dilution in liquid. Raman spectroscopy and X‐ray photoelectron spectroscopy were used to characterize the samples. Raman spectroscopy were employed to show the signature of single‐walled carbon nanotubes and a shift in Raman bands was observed due to the presence of phosphorus in the structure comparing with a reference pristine sample. The shift was attributed to changes in the electronic properties of the material due to doping by phosphorus atoms. XPS spectra confirm the presence of phosphorus bonded to carbons atoms, suggesting the phosphorus incorporation in carbon nanotube structure.